UNDERSTANDING STUDENTS' INTENTION TO USE MOBILE BANKING: IMPACTED BY EASE OF USE, SECURITY, TRUST, AND LIFESTYLE - Rabikhatus Tsania; Nihayatu Aslamatis Solekah (SEAN Institute, 2023)
The digital touch in the banking sector is the development of services provided to customers. One form of digital touch made by banks is mobile banking. Customer interest in using mobile banking continues to increase every year and of course this interest is based on several factors. The purpose of this study was to determine the effect of ease of use, security, trust and lifestyle on the interest in using mobile banking. This type of research is quantitative research. The object of this research is students who use mobile banking in the city of Malang as many as 221 respondents. The sampling technique used purposive sampling. The data collection technique uses a questionnaire distribution technique. Data analysis method used through 3 tests, namely instrument test, classical assumption test, and statistical test. The tool used is IBM SPSS Statistics 26. Based on the results of research that has been done, it can be seen that the ease of use and lifestyle variables partially influence the interest in using mobile banking. Meanwhile, the security and trust variables do not partially influence the interest in using mobile banking. However, simultaneously the variables of ease of use, security, trust, and lifestyle influence the interest in using mobile banking.